Ag-based electrocatalysts for ethylene epoxidation. (20th October 2021) - Gilbert, B.; Cavoue, T.; Aouine, M.; Burel, L.; Aires, F.J. Cadete Santos; Caravaca, A.; Rieu, M.; Viricelle, J.P.; Bruyère, S.; Horwat, D.; Migot, S.; Vilasi, P.; et al.
Highlights: Self-redispersion on stream of Ag on YSZ leading to selective Ag clusters. Advanced Ag/GDC electrocatalytic coatings prepared by reactive magnetron sputtering. Ethylene can be electrooxidized into ethylene oxide on Ag/GDC electrodes. Key role of O 2− ionic species in the mechanism of the ethylene epoxidation. Abstract: Ethylene oxide (EO) is industrially produced by epoxidation of ethylene on Ag-based heterogeneous catalysts. Electrophilic oxygen species are assumed to be active key species in the EO production. This study explores the possibility to electrochemically produced these oxygen species in a solid oxide electrochemical cell. Two series of Ag based cermet electrodes were prepared either with Yttria Stabilized Zirconia (YSZ), a pure oxygen ionic conductor, or with Gadolinia-Doped Ceria (GDC), a mixed ionic and electronic conductor. Ag/YSZ cermet layers were deposited on planar and tubular YSZ dense substrates by using a conventional chemical method while Ag/GDC cermets were coated on GDC dense pellets by reactive magnetron sputtering. We evidenced a self-redispersion of Ag in the ethylene/oxygen mixture in Ag/YSZ cermet layers leading to the formation of small Ag clusters in close interaction with YSZ which are selective for epoxidation. However, the sintering process of these small Ag clusters is too fast even at 260°C to maintain the EO selectivity. On the other hand, the selectivity towards EO and the ethylene conversion of Ag/GDC cermet coatings were found to linearly increase with the applied current, demonstrating for the first time, the direct electrooxidation of ethylene into EO. Graphical abstract: Image, graphical abstract